Gender disparity in dermatologic society leadership: A global perspective - Dalia Limor Karol, MD; Laura Sheriff, BSc; Sabeena Jalal, MD, PhD; Jeffrey Ding; Allison R. Larson, MD; Rachel Trister; Faisal Khosa, MD, MBA, FFRRCSI, FRCPC (Wolters Kluwer, 2021)
Background: In the last half-century, there has been increased representation of women in medicine. Despite this increase, there continues to be underrepresentation of women in medical leadership positions. The objective of this study was to investigate the phenomenon of gender disparity in the leadership of professional societies of dermatology worldwide. Methods: Online databases were used to extract the names of global dermatologic societies. Individual society websites were accessed to obtain information on executive members. Data not available on society websites were obtained through internet searches. Scopus was used to obtain H-indexes and other bibliometric outcomes. Results: Our data collection spanned 92 countries, with 1733 society leaders identified and information available for 1710. In North America, Europe, Asia, Australia, and the Middle East, women were in a minority in dermatology professional society leadership. In South America, Central America, and Africa, women were in a slight majority. Across all professional societies, the role of president was more frequently held by men (n = 95) as opposed to women (n = 75). Female leaders were less likely to hold concurrent academic positions as deans/chairpersons/directors (83.33%) than their male counterparts (92.06%). The median H-index of female leaders (9) was lower than that of men (14). Conclusion: Gender disparity exists in leadership positions in professional dermatology societies. Cultural/continental specific factors should be explored further. Enhancement of institutional support, mentorship, and sponsorship for female dermatologists should be encouraged.